Thoracodorsal artery perforator flap: Indeed a versatile flap - Leena Jain; Samir M. Kumta; Shrirang K. Purohit; Rashmi Raut (Indian Journal of Plastic Surgery)
Introduction: The thoracodorsal artery perforator (TDAP) flap has emerged as one of the ideal perforator flaps. We, hereby, describe its versatility in indications (free/pedicled), methods of harvest (patient position and paddle orientation) and perforator consistency. Materials and Methods: We have performed a total of six TDAP flaps-five free and one pedicled, over a period of 1-year from March 2014 to February 2015 at a single centre. Our indications have been: Reconstruction of oral cavity, breast and upper and lower extremities. Results: We had neither any failures nor any re-explorations. The average perforator length is about 6 cm and the pedicle length can be extended to 12-14 cm by including the thoracodorsal artery. There is inconsistency in perforator position; however, the presence of a perforator is certain. It can be harvested in lateral, prone or supine position, thus, does not require any position change allowing a two-team approach to reconstruction. The paddle can be oriented vertically or horizontally, both healing with scars in inconspicuous locations. Apart from providing a good colour match for extremities, this flap can be thinned primarily. Conclusion: The versatility of TDAP has several advantages that make it a workhorse flap for most reconstructions requiring soft tissue cover. Further, the ease of harvest makes it a good perforator flap for beginners. Its use in chimerism with the underlying latissimus dorsi muscle provides reconstruction for coverage and volume replacement.